Analisis Kompetensi Siswa pada Ujian Nasional Berbasis Kertas Pensil (UNKP) dan Berbasis Komputer (UNBK) pada Mata Pelajaran Fisika SMA Negeri 4 Kendari (Studi Kasus: UN Tahun 2015-2018) - Zhahir, Ilma; Erniwati, Erniwati; Sahara, La (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to comprehend student's competency in PBT national exam in 2015 and CBT national exam at 2016-2018 valued by the material units and the average result of students. This study was conducted by qualitative approach combines with descriptive method. Where the subject is the exam result of certification students. The data was collected by documentation taken of the school authorities who analyzed the result of national exam in SMA 4 Kendari. Then, it could be concluded that according to the material unit, the heat and thermodynamics valued as the highest number that the average stood on 2015 and 2017, the measurement unit and cinematic were on 2016 and 2018. The subjects of electricity, magnetic, modern physics got the lowest average on 2015, 2017, and 2018. While on 2016 was the of wave and optic. In generally, the average National Exam score and student’s competency achievement decreases every years.